Search For Existence In Fatima Mernissi's Dreams Of Trespass Novel ( 1994 ): An Existentialist Approach - Gemiati, Yuni (2012)
This study is about search for existence in Dreams of Trespass novel. The objective of this study is to apply the existentialist approach to analyze the search for existence of women's existence in Dreams of Trespass. The data source come from primary data source that is the novel and the secondary data source are biography of the writer, website and related with the novel. The method of the data collection is descriptive analysis. The writer uses Sartre's major point of existentialism to answer the problem of the study. The study is descriptive qualitative research whose data are taken from novel. The technique of the collecting data is library research, while the technique of analyzing data is descriptive. The study comes to the following conclusions. Firstly, based on the structural analysis of each elements, it shows that character and characterization, setting, plot, point of view, style, theme are related to each other and form the unity. Secondly, based on the existentialist analysis the writer wants to say that women can show her existence to get opportunity, equal status, and freedom to choose their own ways to achieve success.